How University Students Assess Their Water Skills - Dimitrić, Goran; Jakšić, Milorad; Sadri, Filip; Šajber, Dorica; Kaurin, Tanja; Zenić, Nataša; Tabakova, Elena (Frontiers in Sports and Active Living, 2022)
Water competencies are one of the drowning prevention measures. Knowing your own abilities in water can be an important factor in water safety for each individual. On a sample of 150 students (male/female) from the faculty of sport and physical education, ages 19-20, a cross-sectional study was conducted to identify the relationships between perceived and real water competency and perceptions of drowning risk. The results of this study confirmed gender differences in actual and perceived water abilities. The participants had inaccurate perceptions of their own water abilities. Both male and female students, with high precision, assessed their ability to swim long distances (rs=0.601; rs=0.694) just as female students assessed their ability to float (rs=0.698). Male students greatly overestimated their backstroke swimming, while female students underestimated their ability to dive into the water. Both groups overestimated underwater swimming and underestimated their surface dive skill. When assessing the risk, the male students claimed that there was no particular risk when capsized canoe 100m offshore and swept off an isolated rock while fishing. Male students are more prone to overestimating their abilities than female students.